2016
DOI: 10.1111/nph.14129
|View full text |Cite
|
Sign up to set email alerts
|

The Eucalyptus linker histone variant EgH1.3 cooperates with the transcription factor EgMYB1 to control lignin biosynthesis during wood formation

Abstract: Summary Wood, also called secondary xylem, is a specialized vascular tissue constituted by different cell types that undergo a differentiation process involving deposition of thick, lignified secondary cell walls. The mechanisms needed to control the extent of lignin deposition depending on the cell type and the differentiation stage are far from being fully understood. We found that the Eucalyptus transcription factor EgMYB1, which is known to repress lignin biosynthesis, interacts specifically with a linke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 54 publications
(89 reference statements)
1
32
1
1
Order By: Relevance
“…In this respect, we found that the upregulation in holm oak of the putative ortholog of Eucalyptus EgMYB1 and Arabidopsis FLC. EgMYB1 can interact with a linker histone and it has been hypothesized that it represses the phenylpropanoid biosynthetic enzymes through chromatin remodeling (Soler et al 2017). FLC (FLOWERING LOCUS C) is a floral repressor that integrates vernalization responses (Sheldon et al 2000) and in perennial trees an FLC-like gene has also been highlighted as a candidate for bud dormancy regulation (Porto et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, we found that the upregulation in holm oak of the putative ortholog of Eucalyptus EgMYB1 and Arabidopsis FLC. EgMYB1 can interact with a linker histone and it has been hypothesized that it represses the phenylpropanoid biosynthetic enzymes through chromatin remodeling (Soler et al 2017). FLC (FLOWERING LOCUS C) is a floral repressor that integrates vernalization responses (Sheldon et al 2000) and in perennial trees an FLC-like gene has also been highlighted as a candidate for bud dormancy regulation (Porto et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of Eucalyptus gunni EgMYB1 in thale cress and poplar negatively regulates SCW formation, including lignin biosynthesis [45]. When interacting with the linker histone variant EgH1.3, EgMYB1 displays stronger repressive activity, thereby preventing premature lignification of xylem cells during their early stages of differentiation [46]. The two orthologs of EgMYB1 in Populus deltoides and P. tomentosa (PdMYB221 and PtoMYB156) also reduce the SCW thickness of xylem fibers and the content of cellulose, lignin, and xylan [47,48].…”
Section: R2r3 Mybs the Gatekeepers Of Scw Formation And Lignificationmentioning
confidence: 99%
“…During this developmental process, xylem initial cells produced by the meristematic vascular cambium undergo elongation, secondary cell wall (SCW) deposition, lignification and finally programmed cell death (in the case of fibres and vessels) in a narrow tissue layer within the stem 3, 4 . The process is likely to be extensively regulated at the chromatin level, as demonstrated for example through the regulation of lignification by histone H1.3 in Eucalyptus 5 . The majority of plant epigenomic studies, however, have been based on whole organs or complex mixtures of tissues that provide limited resolution of cell- or tissue-specific epigenetic regulation during development.…”
Section: Introductionmentioning
confidence: 99%